Implementasi Pembelajaran Aktif Berbasis Online Bagi Guru-guru Sekolah Dasar Gugus Kaktus Bangkinang-Kabupaten Kampar - Mahdum Muhammad Adnan; Hadriana Hadriana; Riki Apriyandi Putra; Dedi Futra; Indra Primahardi (Journal of Community Engagement Research for Sustainability, 2021)
In the era of the Industrial Revolution 4.0, learning systems that still use paper based or face to face learning must be transformed into learning activities based on information and communication technology (ICT). A teacher must be able to use ICT as a tool to make the learning process more interesting, effective and efficient. The purpose of this activity is to provide technical guidance for teachers of the Bangkinang Cactus Cluster Elementary School - Kampar Regency in the form of introducing ICT concepts in schools, using interactive learning applications, and designing active learning scenarios through online learning according to the subjects taught. The Online-Based Active Learning Design Training activity was held in Kampar Regency. The teachers who are members of the Cactus Cluster consist of teachers from 6 elementary schools. The implementation stage begins with a pretest, which aims to determine the participants' initial knowledge. This activity fosters motivation for teachers to design classroom learning activities using active learning methods. Teachers obtain information and are also guided in designing active learning scenarios, designing Productive, Imaginative and open-ended questions and also designing worksheets and assessment sheets.